2019
DOI: 10.5114/aoms.2017.72405
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinases, inhibitor of metalloproteinases mRNA and protein expression in laryngeal squamous cell carcinoma

Abstract: Introduction The aim of the study was to investigate the mRNA expression and protein levels of matrix metalloproteinases (MMP) 2 (MMP-2), 9 (MMP-9), 7 (MMP-7) and their tissue inhibitor TIMP-2 in patients with laryngeal squamous cell carcinoma and control subjects and additionally to evaluate a possible correlation with clinicopathological features. Material and methods The expression levels of MMP-2, MMP-9, MMP-7, and TIMP-2 mRNA were detected by the real-time quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 29 publications
(42 reference statements)
3
6
0
Order By: Relevance
“…Riedel et al discovered the elevation of serum MMP-9 levels in patients with head and neck SCC [ 43 ], which is also observed by Stanciu et al [ 44 ]. Lotfi et al reported that both serum MMP-2 and MMP-9 levels were significantly increased in laryngeal SCC cases compared with healthy controls [ 45 ], and similar results were depicted by Matulka et al and Grzelczyk et al [ 46 , 47 ]. Choudhry et al revealed that serum levels of MMP-1, − 8, − 10, − 12 and − 13 in oral SCC patients were substantially elevated as compared with healthy controls [ 48 ].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Riedel et al discovered the elevation of serum MMP-9 levels in patients with head and neck SCC [ 43 ], which is also observed by Stanciu et al [ 44 ]. Lotfi et al reported that both serum MMP-2 and MMP-9 levels were significantly increased in laryngeal SCC cases compared with healthy controls [ 45 ], and similar results were depicted by Matulka et al and Grzelczyk et al [ 46 , 47 ]. Choudhry et al revealed that serum levels of MMP-1, − 8, − 10, − 12 and − 13 in oral SCC patients were substantially elevated as compared with healthy controls [ 48 ].…”
Section: Discussionsupporting
confidence: 66%
“…Measurement of serum MMP levels in patients with SCC of different anatomic sites, and comparison of the results with those of healthy controls have been documented [42][43][44][45][46][47][48][49][50]. Jiao et al showed that patients with esophageal SCC had significantly higher serum MMP-13 levels than healthy controls; furthermore, serum MMP-13 levels were found to be associated with tumor progression and survival [42].…”
Section: Discussionmentioning
confidence: 99%
“…MMP‐9 mediates pepsin‐induced mucin 5AC expression in airway epithelial cells contributing to hypersecretion and inflammation, 73 is induced by TGF‐β signaling in tracheal cells, a key pathway in laryngotracheal stenosis, 74 is elevated in mild and severe GERD, 75 and plays a role in the early inflammatory response in a model of Barrett's esophagus (BE) 76 . MMP‐2, 7 and 9 have been implicated in laryngeal cancer 77 . MMP‐1 is a pre‐invasive factor for BE associated with GERD severity and esophageal adenocarcinoma (EAC) 78,79 .…”
Section: Discussionmentioning
confidence: 99%
“…Laryngeal squamous cell carcinoma (LSCC) is a multifactorial disease characterized by frequent metastasis in lymph nodes early during disease onset, and represents the most common form of head and neck malignancies 1 . Recent evidence indicates a clear association between altered growth factor receptors-mediated intracellular pathways and biological processes underlying LSCC that induce changes in the extracellular matrix (ECM) 2,3 . Lumican is an important ECM protein that belongs to a class II small leucine rich proteoglycans and has four potential N-glycosylation sites 4 .…”
Section: Introductionmentioning
confidence: 99%